EFFECT OF CHARCOAL APPLICATION ON THE EARLY GROWTH STAGE OF Acacia mangium and Michelia montana - Siregar, Chairil Anwar (Indonesian Journal of Forestry Research, 2007)
Charcoal, or black coloured carbon-predominated stuff, is produced during incomplete combustion of  woody plant biomass. Charcoal application to the soil can improve chemical and nutritional nature thereby inducing better plant growth and development. However, the utilization of charcoal in forestry sector, especially industrial plantation, has not been introduced due to the absence of available information.  Indicator species used in this study are Acacia mangium and Michelia montana. A. mangium is one of  the most important species grown in industrial plantations in Indonesia. Meanwhile M. montana is critical endemic species in Gunung Halimun National Park. Glasshouse research was designed to examine the effectiveness of charcoal incorporation into marginal soils on the growth of 6-month-old Acacia mangium and 6-month-old Michelia montana. Charcoal treatments were 0,10, 15 and 20% (v/v) for A. mangium, while 0, 5, 10, 15 and 20 % (v/v) for M. montana. Representative samples of Orthic Acrisol (i.e. Very fine, mixed, semiactive, isohyperthermic, and Typic Paleudult) were collected from B horizon. A completely randomized design with four replications (for A. mangium) and five replications (for M. montana) was employed to examine the effect of charcoal application on the plant growth and some important chemical properties of  the corresponding soil. Charcoal additions to the soil significantly increased height, diameter, and leaf and stem biomass weight of A. mangium, and significantly increased height, diameter, and total biomass weight of  M. montana seedlings in comparison to those of a control.  Increasing the amount of charcoal higher than 10% level, however, have little effect on A. mangium growth. On the other hand, increasing the amount of charcoal higher than 10% is still effective on M. montana growth. This study indicated that charcoal application at the rates of 10 % for A. mangium and 15 % for M. montana would be adequate to improve the availability of soil nutrients, and hence significantly induce a better plant growth response.